Cyclooxygenase 2 Effector Genes as Potential Inflammation-Related Biomarkers for Colorectal Cancer Circulating Tumor Cells Detection by Liquid Biopsy - Stamatakis, Konstantinos; Torres-Gérica, Patricia; Jiménez-Segovia, Alba; Ramos-Muñoz, Edurne; Crespo-Toro, Lorena; Fuentes, Patricia; Toribio, María L.; Callejas-Hernández, Francisco; Carrato, Alfredo; García Bermejo, María Laura; Fresno, Manuel (Frontiers in Pharmacology, 2022)
Cyclooxygenase 2 (COX2) has been implicated in cancer development and metastasis. We have identified several COX2-regulated inflammation-related genes in human colorectal cancer cells and shown that some of them play important roles in tumor progression. In this work, we have studied the COX2-regulated genes in the mouse colorectal cancer cell line CT26, to find that many are also regulated by COX2 over-expression. On the other hand, we generated a CT26 cell line expressing Gfp and Luciferase, to study tumor growth and metastasis in immunocompetent Balb/c mice. We then collected solid tissue, and blood samples, from healthy and tumor bearing mice. Using the Parsortix® cell separation system and taking advantage of the fact that the tumor cells expressed Gfp, we were able to identify circulating tumor cells (CTCs) in some of the mice. We compared the mRNA expression levels of Ptgs2 and effector genes in the samples obtained from tumor bearing or healthy mice, namely tumor or healthy colon, ficoll purified buffy coat and Parsortix-isolated cells to find different patterns between healthy, tumor bearing mice with or without CTCs. Although for genes like Il15 we did not observe any difference between healthy and tumor bearing mice in ficoll or Parsortix samples, others, such as Egr1, Zc3h12a, Klf4 or Nfat5 allowed to distinguish for cancer or CTCs presence. Gene expression analysis in ficoll or Parsortix processed samples, after liquid biopsy, may offer valuable diagnostic and prognostic information and thus should be further studied.